Complication Profile of Total Submuscular Versus Prepectoral Tissue Expander Placement: A Retrospective Cohort Study. (23rd June 2022) - Soni, Sara E.; Le, Nicole K.; Buller, Mitchell; Modica, Ashley D.; Kumar, Ambuj; Smith, Paul D.; Laronga, Christine
Abstract : Background: We sought to compare the safety profile of prepectoral breast reconstruction with total submuscular tissue expander reconstruction, previously our standard. Primary outcomes of interest in this retrospective cohort study were incidence of infection, hematoma, seroma, mastectomy flap necrosis, and reconstruction loss. Methods: Total submuscular and prepectoral with acellular dermal matrix reconstructions consecutively performed by a single surgeon (P.D.S.) between January 1, 2016, and December 31, 2019, were compared. Demographic and clinical characteristics, as well as complications and complication types, were extracted for all patients. A t test was used to assess differences in continuous variables. Multivariate logistics regression was used to assess the association between type of reconstruction and complication rate. The statistical significance was set at 0.05 for all comparisons. Results: A total of 133 patients (234 breasts) were included. There was a significantly greater incidence of infection (16.5% vs 5.5%, P < 0.01) in the prepectoral/acellular dermal matrix cohort. However, reconstructive loss was low in both cohorts (2.5% and 3.0%, P = 0.83). Adjusted odds ratio for complications in the prepectoral cohort was 2.26, but this was not statistically significant (adjusted P = 0.24). Conclusions: Prepectoral breast reconstruction shares an overall complication profile that is not greater than that of total submuscular reconstruction. It is associated with a greater risk of infection; however, the ability to salvage the reconstruction with early, aggressive intervention results in low rates of reconstructive loss, comparable with those of total submuscular reconstruction.